Pembangunan Sistem Ujian Harian Siswa Berbasis Web Dengan Mengacu Pada Standar Kualitas ISO 25010 - Syehka Sofia Arya Larasati; Denny Sagita Rusdianto; Tri Astoto Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The daily exams which have been held in SMPN 3 Nglegok have some problems. There are only three variations different types of random questions. However the answer does not have many variations which makes students will be able to cheat easily. In the other hand, the long way process of examination is assumed as time consuming activity starting from students' process in doing the test, the process of assessing student answers by the teacher, the process of recaping the student score until the student's score announcement. In order to overcome these problems, an online daily test system is built to fasten the process of daily test. This system has been successfully tested with unit testing and integration testing using white box testing method then validation testing using black box testing method. The results of all three tests are valid. The system was tested with ISO 25010 quality model, the result of validity functional suitability test was valid with 100% success rate. Characteristic of performance efficiency at subcharacteristic of time behavior has average 0.30 seconds, subcharacteristic of resource utilization has RAM Â± 1.460 MB and CPU Â± 0.10%, subcharacteristic of capacity has maximum 132 users. Characteristic of compatibility is valid. Characteristics of usability has percentage score 87.7% or very feasible. Characteristics of reliability at subcharacteristic maturity has no error when it was given 132 users as burden, subcharacteristics availability has valid value. Characteristics of security in the subcharacteristic of confidentiality, integrity and non-repudation resulted in a safe of security level. the subcharacteristic of accountability can record user activity and authenticity subcharacteristic is valid.